Where Is Equity in HiAP?; Comment on "A Realist Explanatory Case Study Investigating How Common Goals, Leadership, and Committed Staff Facilitate Health in All Policies Implementation in the Municipality of Kuopio, Finland" - Michelle Amri; Jesse B. Bump (Kerman University of Medical Sciences, 2023)
Health equity is no longer a central feature of Health in All Policies (HiAP) approaches despite its presence in select definitions of HiAP. In other words, HiAP is not just about considering health, but also health equity. But as HiAP has become more mainstream, its success around health equity has been muted and largely non-existent. Given the normative underpinning and centrality of equity in HiAP, equity should be better considered in HiAP and particularly when considering what 'successful' implementation may look like. Raising health on the radar of policy-makers is not mutually exclusive from considering equity. Taking an incremental approach to considering equity in HiAP can yield positive results. This article discusses these ideas and presents potential actions to restore HiAP's once central equity objectives, which include: seeking synergies focused on health equity with those who hold different convictions, both in terms of goals and measures of success; considering the conditions that allow HiAP to be fostered, such as good governance; and drawing on research on HiAP and other multisectoral approaches.